Atividade antimicrobiana de extratos de folhas, caules e raízes de Eugenia klotzschiana O. Berg (Myrtaceae) - Vicente, Edgar Oliveira (Universidade Federal de São Carlos, 2020)
Since the discovery of penicillin by Alexander Fleming, the phenomenon of antibiotic resistance has been observed. Economic and technological factors have influenced the drug industries and decreased or ceased research focusing on new antibiotics. In such a way, the Antibiotic Crisis was established, culminating in a growing expenditure on hospital expenses and an increase in medication dosages. Microorganisms such as Escherichia coli, Candida albicans and Staphylococcus aureus are among the most common causes of hospital infections that are difficult to treat. Therefore, research with natural products has been indicated as a promising strategy for obtaining new antibiotics. Secondary plant metabolites, especially the Myrtaceae family, have shown satisfactory results for this purpose. However, this work presents antimicrobial results from extracts obtained from leaves, stems and roots of Eugenia klotzschiana with different solvents of varying polarities.
Antimicrobial activity from leaves, stems and roots extracts to Eugenia klotzschiana O. Berg (Myrtaceae)
Keywords: Extração a frio; Infusão aquosa; Maceração etanólica; Pêra-do-cerrado; Potencial antibiótico; Maceration; Infusion; Ethanolic; Aqueous; Eluotropic; Myrtaceae; CIENCIAS BIOLOGICAS::BOTANICA